Sea snakes in Australian waters (Serpentes: subfamilies Hydrophiinae and Laticaudinae)—a review with an updated identification key - Rasmussen, Arne Redsted; Sanders, Kate Laura; Guinea, Michael L.; Amey, Andrew P. (Zootaxa, 2014)
Sea snakes (Elapidae, subfamilies Hydrophiinae and Laticaudinae) reach high species richness in the South China Sea and in the Australian region; however, most countries in the two regions still lack up-to-date checklists and identification tools for these snakes. We present an updated reviewed checklist and a new complete identification key to sea snakes in Australian waters. The identification key includes 29 species documented and 4 possibly occurring taxa and is based mostly on easy-to-use external characters. We find no evidence for breeding populations of Laticauda in Australian waters, but include the genus on the list of possibly occurring taxa.